Die Transmission über den Zinskanal: von der Geldpolitik zur Kreditnachfrage - Daniel Hagemann; Monika Wohlmann (Wirtschaftsdienst, 2017)
Der Anfang der Finanz- und Eurokrise liegt nun bald zehn Jahre zurück. Angesichts der drastischen geldpolitischen Maßnahmen zur Eindämmung der Krise hatten viele Marktteilnehmer mit einer schnelleren Normalisierung der Situation gerechnet. Warum hat die Geldpolitik nicht mehr Wirkung gezeigt? Die Autoren untersuchen den Zinskanal als einen der wichtigsten Transmissionsmechanismen der Geldpolitik auf die Realwirtschaft und deren Kreditnachfrage. Neben einer kurzen Darstellung der theoretischen Wirkungsweise wird die Wirkungskette des Zinskanals analysiert und auf hemmende Faktoren hin untersucht. – – Through more favourable funding costs for commercial banks, the central bank can send expansionary monetary stimuli into the real economy to boost the demand for credit. In this regard, one of the most important channels for the transmission of monetary policy is the interest rate channel. This contribution analyses the effectiveness of the interest rate channel in the eurozone. It comes to the conclusion that the transmission of the expansive monetary stimulus into the banking sector works well, but that the transmission of the stimulus to the real economy is partly inhibited. The main factors that dampen credit demand are higher real interest rates as well as low growth and higher indebtedness, especially in the eurozone's peripheral countries.
Keywords: E52; E44; G21; 330